KUALITAS DAN NILAI PELAYANAN BALAI ARKEOLOGI YOGYAKARTA DALAM PENGELOLAAN HASIL PENELITIAN KEPADA PUBLIK - Nurani, Indah Asikin (BRIN, 2009)
Balai Arkeologi Yogyakarta is a research institution which serves the public on informations concerned with researches on archaeology. On the other hand, the results of those researches have to be informed to the society, since it is supposed to have many benefits for the academic and the public. This article is intended to express the result of the public appreciation for the service done by Balai Arkeologi Yogyakrta, using measurement of service (tangible, empathy, responsive, reliability and assurance) and the comparison between the benefits and the cost.